Waste Footprint of Selected City Districts of Prague - Vološinová, Dagmar; Ansorge, Libor (European Journal of Sustainable Development, 2021)
The growing population, thriving economy, rapid urbanisation significantly accelerate the generation of municipal waste. Tightening conditions for waste management are a challenge for all stakeholders to comply with the law and, at the same time, motivate them to reduce waste production. The knowledge of the biosphere's assimilation capacity can quantify the environmental impact of waste in an understandable and popular form to better understand the human need to assimilate the waste produced. Utilising the waste footprint indicator and anthropogenic emissions in the form of waste are converted into soil adsorption capacity. The article compares the waste footprints of different areas of the city of Prague. It quantifies the influence of living and waste services on the waste footprints of the capital inhabitants. This article also discusses the relationship of the waste footprint with other footprints and is intended to inform future debate on trace accounting.